O ensino de história na contemporaneidade: tecnologias digitais, internet e inclusão digital - Souza, Maria do Socorro (Universidade Federal Rural do Semi-Árido, 2019)
The present study aims to analyze how the pedagogical uses that the teacher of History of public schools in Mossoró/RN makes of digital technologies, especially the internet, can contribute to the digital inclusion of the student and its consequent social inclusion. Overcoming the traditional notion of digital inclusion as a democratization of access to Digital Technologies of Information and Communication, the term is here understood as the access to digital artifacts, the technical-operational domain and, more importantly, its critical, authorial and reflexive use. Throughout the text, the critical insertion of digital technologies in the teaching of History is strongly defended, given its potentialities in the field of information, communication and interaction and the transformations that have been provoking in contemporary life forms. Such changes are reconfiguring the notions of time, space, knowledge, of established contexts and identities. For this reason, the uses of technologies need to be made from new pedagogical models, in harmony with the innovations brought by them, so that the digital inclusion of the student and the development of his critical thinking happen, enabling him to perceive himself as a citizen and subject of the history. The analysis of the uses of the digital technologies to the promotion of the digital inclusion of the student of History is carried out through a qualitative field study, of explanatory nature, whose universe are teachers of History of the public network of education. The semi-structured interview and observation are the techniques used to produce data. As part of the research, aiming to collect possibilities of uses of digital technologies for the teaching of History, in order to stimulate the critical insertion of these artifacts in the classroom of this discipline and, thus, to favor the digital inclusion of the student, a virtual portal was created through a bibliographical study. The theoretical contribution on digital technologies, cyberspace and its effects on society and education was given, among others, by André Lemos (2003, 2008), Heinsfeld and Pischetola (2017), José Manuel Moran (2013, 2015, 2017), Marc Prensky (2001, 2012) and Pierre Lévy (1996, 1998, 1999, 2007). In order to base the debate on the teaching of History, methods and strategies, and their relation with digital technologies and cyberspace, authors such as Circe Bittencourt (1993, 2011, 2017), Elza Nadai (1992), Eucídio Pimenta Arruda (2011, 2013, 2014), Fonseca (2010), Guimarães (2012) and Itamar Freitas (2010) were used. Maria Helena Bonilla (2005, 2009), Bonilla and Nelson Pretto (2011), Lemos (2007, 2009, 2011) and Manuel Castells (2002, 2003, 2005) are the theorists through which digital inclusion is discussed as a means for the social inclusion and the exercise of citizenship. Regarding the pedagogical uses of digital technologies in the teaching of History, the results of the research pointed out that, when performed in a critical, collaborative, planned and authorial way, they favor the digital inclusion of the student, even if such inclusion does not occur in a full manner.
Keywords: Ensino de História; Inclusão digital; Inclusão social; Teaching of History; Digital technologies; Digital inclusion; Social inclusion; Tecnologias digitais; MULTIDISCIPLINAR::ENSINO